Toward diverse seed sourcing to upscale ecological restoration in the Brazilian Cerrado - Silva, Mateus C.; Moonlight, Peter; Oliveira, Rafael S.; Pennington, R. Toby; Rowland, Lucy (Frontiers in Ecology and Evolution, 2022)
Seed markets are vital to scaling up ecosystem restoration in the Brazilian Cerrado, home of the world’s most species-rich grasslands and savannas. We compiled lists of species traded by four major Cerrado seed supply systems to investigate the representativeness of the species currently available for seed-based restoration. We also identified whether dominant ground-layer species are being sourced for seed production. Seeds from 263 Cerrado species can be purchased for restoration, of which 68% are trees, particularly legumes (24%). 63% of the traded species were found in only one seed supply system. The five most dominant graminoids of the Cerrado ground layer were available for sale, but two additional species uncommon in old-growth areas represented 44% of the sales of a key seed trader in Central Brazil. The expansion of Cerrado seed supply systems should be supported to further increase the number of species on the market. Sourcing seeds from a diversity of herbaceous species is central to facilitating the restoration of species-rich grasslands and savannas in the Cerrado. Recovering the diversity and functioning of old-growth open ecosystems through seeds will depend on increasing the supply and demand for species typical of Cerrado’s ground layer.